PERSEPSI MAHASISWA AKUNTANSI STIE NASIONAL BANJARMASIN TENTANG EXPECTATION GAP DAN TANGGUNG JAWAB AUDITOR - Ferra Maryana; Rakhmi Ridhawati; Igna Elmoulika (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This research aimed to give empirical evidences about the difference perception between accounting student which had job experience and not had job experience. The variables in this study were expectation gap and auditor responsibilityThe population in this research was the accounting students in STIE Nasional Banjarmasin. The data collected from the output of questionnaires which gived to the respondents. The samples technique used purposive sampling with 52 samples.The research gived empirical evidences that there were no different between accounting student which had job experience and not had job experience about expectation gap but there were different between accounting student which had job experience and not had job experience about auditor responsibility.